Nikah Siri Perspektif Islam dan Kristen:: Studi Kasus KUA Kec. Medan Area - Herman, Nurwinda; Pardede, Hasrima Dinda (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Marriage is a sacred and noble contract between a man and a woman as legal husband and wife with the aim of achieving a sakinah, mawaddah wa rahmah family, full of wisdom and mutual support. Islam advocates for marriage. Because it has a good influence on the perpetrators themselves, society and all mankind. Lately, the phenomenon of unregistered marriage has given an interesting impression. First, unregistered marriage seems to have really become a trend that is not only practiced by the general public, but also practiced by community figures who so far are often referred to by the terms kyai, dai, ustad, cleric, or other terms that mark a person's ability to study religion. (Islam). Second, unregistered marriage is often placed as an option when someone wants to be polygamous for a number of reasons. Keywords: Siri Marriage, Islamic Perspective, Christian Perspective